STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN DI SHOWROOM MOBIL PT. ANZON AUTO PLAZA - Ekawati, Tri; Sahputra, Rachmat; Tawil, Hamzah (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research analyzes the role of marketing strategies in increasing sales of PT Anzon Auto Plaza's car showroom in the midst of fierce competition in the Indonesian automotive industry. This research uses a qualitative descriptive design by collecting primary and secondary data through observations, interviews, and internal company sales data. The results of the analysis show that MPV models, particularly Avanza and Calya, are the best-selling vehicle models, which may be influenced by effective discount promotions. The time trend shows that despite an increase in demand for motor vehicles due to economic growth and urbanization, PT Anzon Auto Plaza experienced a 23% decrease in sales during the period January to March 2023, possibly influenced by seasonal factors such as the month of Ramadan and economic fluctuations. Increased sales at the beginning of the year, possibly influenced by economic factors. Based on the research results, it is recommended that PT Anzon Auto Plaza implement a stronger marketing strategy during February and March, diversify the product portfolio, continue promotional programs that have proven effective, conduct more in-depth market research, and evaluate the success of MPV models to improve the marketing strategy of other models.